Resiliensens åbenbaringer:: Fra den ideologiske afvæbning af katastrofen til (p)anarkiets revolutionære implikationer - Hornborg, Alf; Kristensen, oversætter, Nathalie Keighley (Slagmark - Tidsskrift for idéhistorie, 2018)
The currently burgeoning discussions on ‘socio-ecological resilience’ tend to mask the power relations, contradictions of interest, and inequalities that to a large extent determine how humans utilize the surface of the Earth. Resilience theory has the potential to radically confront such power structures by identifying some of the basic assumptions of economics as the very source of vulnerability, mismanagement, and crises. It has every reason to critically scrutinise the operation of general-purpose money, the global market, and neoliberal ideology. The ultimate implications of resilience theory, in other words, are vastly more radical and subversive than its current proponents imagine. A strategy to enhance socio-ecological resilience would be to distinguish local from global economic scales by employing separate currencies for the two levels. Proponents of resilience theory are advised to engage more respectfully with social science, particularly its understandings of culture and power. Upon doing so, they would find the idea of a bi-centric economy, as sketched in this article, entirely consistent with the fundamental insights of resilience theory.